Isometric handgrip exercise impacts only on very short-term blood pressure variability, but not on short-term blood pressure variability in hypertensive individuals: A randomized controlled trial - Otávio A. Bertoletti; Rodrigo Ferrari; Elton L. Ferlin; Ozi M. Barcellos; Sandra C. Fuchs; Sandra C. Fuchs (Frontiers in Physiology, 2022)
Background: The effect of a single isometric handgrip exercise (IHG) on blood pressure (BP) variability (BPV) has not been addressed. This randomized controlled trial evaluated the effect of IHG vs. sham on BPV and BP.Methods: Hypertensive patients using up to two BP-lowering medications were randomly assigned to IHG (4 × 2 min; 30% of maximal voluntary contraction, MVC, with 1 min rest between sets, unilateral) or sham (protocol; 0.3% of MVC). Systolic and diastolic BP were assessed beat-to-beat in the laboratory before, during, and post-intervention and also using 24-h ambulatory BP monitoring (ABPM). BPV was expressed as average real variability (ARV) and standard deviation (SD).Results: Laboratory BPV, ARV and SD variability, had marked increase during the intervention, but not in the sham group, decreasing in the post-intervention recovery period. The overall change in ARV from pre- to 15 min post-intervention were 0.27 ± 0.07 (IHG) vs. 0.05 ± 0.15 (sham group), with a statistically significant p-value for interaction. Similarly, mean systolic BP increased during the intervention (IHG 165.4 ± 4.5 vs. sham 152.4 ± 3.5 mmHg; p = 0.02) as did diastolic BP (104.0 ± 2.5 vs. 90.5 ± 1.7 mmHg, respectively; p < 0.001) and decreased afterward. However, neither the short-term BPV nor BP assessed by ABPM reached statistically significant differences between groups.Conclusion: A single session of IHG reduces very short-term variability but does not affect short-term variability. IHG promotes PEH in the laboratory, but does not sustain 24-h systolic and diastolic PEH beyond the recovery period.